Pengembangan Sistem Informasi Rumah Sakit Sebagai Upaya Pencegahan Fraud Dalam Rangka Peningkatan Layanan Kesehatan pada Rumah Sakit Pemerintah - Ubaidillah, Ubaidillah; Ermadiani, Ermadiani; Rohman, Abdul (Balance : Jurnal Akuntansi dan Bisnis, 2020)
The current National Health Insurance fund policy invites many problems in its implementation. JKN funds leakage caused various government efforts to minimize it through fraud prevention. Management Information System Development can minimize this so that good public service governance can be created over the implementation of JKN funds in government hospitals in the South Sumatra Region through transparency and accountability.This study aims to prove that the Development of Management Information Systems influences the Governance of Public Services at Government Hospitals in the South Sumatra Region through fraud prevention. The results of the study said that the Development of Management Information Systems which is proxied by the Innovation of Management Information Systems affects the Governance of Public Services